ANALISIS KESUKSESAN WEBSITE STIKES ABI (ARTHA BODHI ISWARA) SURABAYA DENGAN MENGGUNAKAN MODEL DELONE & MCLEAN - Denianto, Farid; Sulistiowati, Sulistiowati; Tjandrarini, A.B. (Jurnal Sistem Informasi Universitas Dinamika, 2021)
Sekolah Tinggi Ilmu Kesehatan Artha Bodhi Iswara Surabaya (STIKES ABI) right now is using the website to carry out learning activities, and registration activities. The STIKES ABI website has been created since 2016 and has made many changes every year. The problem with the STIKES ABI website is that the number of visitors has recently decreased. The average number of visitors is 77 per month. Since the beginning of using the STIKES ABI website, there has never been an evaluation of its success. Therefore, in this research, an analysis of the success of services on the STIKES ABI Surabaya website was carried out using the Delone and McLean models which consisted of information quality variables, system quality and service quality as independent variables and usage variables, user satisfaction variables and net benefit variables as dependent variables. This research used 151 samples consisting of 62 active STIKES ABI college students and 89 general society including new students candidate. According to the results of descriptive analysis, obtained the average value of each variable. For the system quality variable obtained an average of 3,54 which means nearly good, for the information quality is 3,62 which means nearly good, for the service quality is 3,51 which means nearly good, for the usage is 3,42 which means good enough, for the user satisfaction is 3,57 users which means nearly good, and the net benefit is 3,61 which means nearly good. Meanwhile, the results of the analysis according to the Structural Equation Modeling (SEM) method showed that the value of the system quality variable that affected the user satisfaction variable by 43,18%, the quality variable had affected the user satisfaction variable by 31,73%, the user satisfaction variable had affected on the usage variable by 45,39% and the user satisfaction variable had affected on the net benefit by 48,77%. Based on the results of this affection, it shows that STIKES ABI Surabaya must improve the system quality and service quality so that is useful to increase user satisfaction of STIKES ABI website. So it can be useful to increase the number of website visitors.